2014
DOI: 10.1016/j.aller.2012.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Safety of immunotherapy in patients with rhinitis, asthma or atopic dermatitis using an ultra-rush buildup. A retrospective study

Abstract: Taking into account the possible bias for the retrospective design of this study we observed that immunotherapy for patients with IgE-mediated diseases using a depigmented polymerized mites extract, with an ultra-rush buildup, has similar frequency of systemic reactions than that seen in slower buildup immunotherapy in other studies. Accelerated buildup could improve patients' adherence and reduce dropout rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 33 publications
1
21
0
8
Order By: Relevance
“…11,12 However, some research indicated that premedication or adjusted doses greatly improved the safety of RIT. 13,14 The systemic adverse reactions in both groups showed no statistically significant differences (P >0.05). In this study, adverse reactions at the build-up phase were examined and compared between RIT and conventional immunotherapy.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…11,12 However, some research indicated that premedication or adjusted doses greatly improved the safety of RIT. 13,14 The systemic adverse reactions in both groups showed no statistically significant differences (P >0.05). In this study, adverse reactions at the build-up phase were examined and compared between RIT and conventional immunotherapy.…”
Section: Discussionmentioning
confidence: 83%
“…This conclusion is similar to that of previous studies. 13,14 In our study, VAS, weekly administration scores, and IgG4 (a marker of ASIT induced immune tolerance) levels in peripheral serum at difference time points between the two groups were compared to evaluate their efficacy. The results demonstrated that VAS in the RIT group was lower at week 2 while the IgG4 levels were higher in the early stage of treatment, and at the point after RIT dose buildup finished 1 week later, weekly medication scores were higher in the conventional immunotherapy group.…”
Section: Discussionmentioning
confidence: 99%
“…187,188 Also, studies indicate that modified allergen extracts are associated with less adverse effects. [189][190][191][192] For aluminum hydroxide containing SCIT products, granulomas have been described from a foreign body reaction mainly caused by incorrect intradermal administration as well as contact allergic reactions, new onset of protein contact dermatitis, or a vasculitis inflammatory reactions have been reported. [193][194][195] If these reactions to SCIT occur, treatment with another aluminum hydroxide-free product is preferred (Grade D).…”
Section: Scitmentioning
confidence: 99%
“…En varias publicaciones se ha reportado que algunos pacientes pueden presentar exacerbación de los síntomas cutáneos con esta terapia; no obstante, cuando la administración se hace de forma controlada, especialmente con extractos modificados, el riesgo de reacciones sistémicas se reduce considerablemente, como se observó en un estudio retrospectivo, también en Medellín, en el cual ninguno de los 114 pacientes con dermatitis, a los cuales se les aplicaron más de 1.000 inyecciones, presentó una reacción sistémica ni tuvo que abandonar la terapia debido a la exacerbación de los síntomas durante el tratamiento (63).…”
Section: Dermatitis Atópicaunclassified
“…Las reacciones sistémicas son infrecuentes (0,1 %) y hasta el momento no se han reportado muertes por esta causa en el país (63), lo cual respondería al hecho de que solo el personal experto en centros especializados se encarga de su aplicación.…”
Section: Consideraciones Particulares Sobre La Inmunoterapia En Colombiaunclassified